Interpretation of composite endpoints in urology: an analysis of citation quality. (4th May 2022) - Jacobsen, Frederik M.; Kvorning Ternov, Klara; Nolsøe, Alexander B.; Østergren, Peter Busch; Fode, Mikkel; Sønksen, Jens; Jensen, Christian Fuglesang S.
Abstract: Objective: To investigate how urological studies using composite endpoints as the primary outcome were cited. Materials and methods: In this quality analysis of citations, three randomized clinical trials each investigating oncological and non-oncological urology were selected for citation analysis based on pre-defined criteria. In total, 531 papers citing the selected studies were reviewed; citations were evaluated based on whether they correctly referred to the composite endpoint and if singleton endpoints were defined and/or discussed. Results: Among the citations, 223/531 (42%) referred to the composite endpoint, of which 217/223 (97.3%) correctly cited the composite endpoint. However, only 91/217 (41.9%) defined and/or discussed the singleton endpoints of the composite endpoint. The lack of a validated instrument for citation analysis was a limitation of this study. Meanwhile, the main strength is the large number of individually analyzed citations. Conclusions: The composite endpoints of urological randomized clinical trials are generally cited without referring to the composite endpoint; when cited, the composite endpoints are described correctly. However, in most cases, without defining or discussing the singleton endpoints.